2020
DOI: 10.1177/2333393620960059
|View full text |Cite
|
Sign up to set email alerts
|

Medical Care-Related Decisions among Patients Diagnosed with Early Stage Malignant Brain Tumor: A Qualitative Study

Abstract: Medical care-related decision-making among patients with malignant brain tumors has not been sufficiently discussed. This study aimed to develop a framework for understanding patients’ experiences in the decision-making process. Semi-structured interviews with 14 patients were analyzed using a grounded theory approach, focusing on their 48 decision-making points. Additionally, interviews with two family members and seven healthcare providers, and participant observations were used to gain contextual insight in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Our review identified cancer anxiety as a strong barrier 22,30 . Numata et al showed in their research on early stage malignant brain tumour that patients experiencing anxiety during treatment decision-making are often driven by the fear of uncertainty of prognosis, their future QoL, and loss of the self 63 .…”
Section: Patient-related Criteriamentioning
confidence: 99%
“…Our review identified cancer anxiety as a strong barrier 22,30 . Numata et al showed in their research on early stage malignant brain tumour that patients experiencing anxiety during treatment decision-making are often driven by the fear of uncertainty of prognosis, their future QoL, and loss of the self 63 .…”
Section: Patient-related Criteriamentioning
confidence: 99%
“…The simplified disease progression scale (FOP-Q-SF) [ 6 ] score, quality of life (QLQ-C30) score, social support scale (SSRS) [ 7 , 8 ], hospital anxiety and depression scale (HADS) [ 9 ] score, and patient dignity inventory (PDI) [ 10 ] scores were compared between the two groups before and after the intervention.…”
Section: Methodsmentioning
confidence: 99%